Financial Situation of Local Government Units During The COVID-19 Pandemic in Poland - Marta KOLODZIEJ-HAJDO (Communications of International Proceedings, 2021)
Under the law, the local governments have been obliged to perform a number of tasks, which are to satisfy the collective needs of the local communities and the development of the local economy. The implementation of these tasks is directly associated with the financial situation of these entities. Any interruptions, crises, and in particular those which cannot be predicted, strongly affect the processes of the economic changes. The crisis caused by the COVID-19 pandemic, in general, has affected the finances of the local governments in Poland. The purpose of the article is to assess the scale of the impact of the COVID-19 crisis on the functioning of the local government units, and on their financial situation. The focus was put mainly on the financial condition of the local governments in Poland after the first year of the pandemic. Legislative actions of the state with regard to counteracting the pandemic and their effect on the communal finances were presented. For the needs of the study, the comparative analysis method was used. The subject of the study were the levels of the revenues, expenses, the budget result, the operational result, the indebtedness of the Polish local governments, regionally. In the survey, the numeric data concerning the years 2018-2020 were used, published by GUS (Central Statistical Office) within the database: Bank Danych Lokalnych, information included in "the Report from Operations of Regional Audit Chambers in 2018, 2019, 2020",  prepared by the National Council of Regional Audit Chambers, and the collective data uploaded on the website of the Ministry of Finance.
Keywords: COVID-19; local government; municipality; Poland